The Analysis of Learning Infrastructure (LI), Learning Motivation (LM) and Economics Learning Achievement (ELA) - Ananda Setiawan; Trisno Martono; Gunarhadi Gunarhadi (Journal of Education and Learning (EduLearn), 2018)
This research aimed to find out whether or not there is an effect of Learning Infrastructure (LI) and Learning Motivation (LM) on Economics Learning Achievement (ELA), and which one has more dominant effect on Learning Achievement, Learning Infrastructure or Learning Motivation. This study was a descriptive quantitative research with survey method. The data of LI, LM and ELA were collected using questionnaire. The population of research consisted of 1192 economics students in Public Senior High Schools of Serdang Bedagai Regency applying the 2013 curriculum. The sample consisted of 300 respondents, taken using cluster areas sampling technique. From the result of research, it can be found that there was a positive significant effect of LI on ELA (tstatistic=9.597, P = 0.000), there was a positive significant effect of LM on ELA (tstatistic=6.990, P=0.000), there was a positive and significant effect of LI and LM on ELA (Fstatistic=114.281, P=0.000), and LI affected ELA more dominantly than LM did.